2011
DOI: 10.4081/ija.2011.e20
|View full text |Cite
|
Sign up to set email alerts
|

Jerusalem artichoke (Helianthus tuberosus L.) productivity in different Italian growing areas: a modelling approach

Abstract: Jerusalem artichoke is considered one of the most interesting crops for inulin production. It has been used to date for the production of low calorie sweetening syrups, dietetic food enriched with fibre, medicines and cosmetics, while more recently, interesting prospects have been opening up for energy uses. The main aspects influencing its adaptability to different pedo-climatic conditions and cropping systems were analysed by implementing CSS (Cropping System Simulator, a simulation model describing crop bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Inulin is a polydispers fructan, which has a degree of polymerization between 4-150 (Baldini et al, 2011). The fructans can be used as dietary fiber in the food industry, and fructose resulting drought strongly influenced tuber yield and inulin content (Monti et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inulin is a polydispers fructan, which has a degree of polymerization between 4-150 (Baldini et al, 2011). The fructans can be used as dietary fiber in the food industry, and fructose resulting drought strongly influenced tuber yield and inulin content (Monti et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Our study expected that physiological traits could be useful for improvement of the crop simulation model to enable it to simulate Jerusalem artichoke productivity in different conditions. Baldini et al (2011) suggested that the crop simulation model could be useful as a tool for the planning and risk evaluation of production Jerusalem as a crop for inulin production.…”
mentioning
confidence: 99%
“…J erusalem artichoke is a perennial warm‐season relative of sunflower ( Helianthus annuus L.), native to temperate regions of North America. This crop is one of the most important crops for industrial inulin production because its carbohydrate‐rich tubers contain 75% inulin on a dry‐weight basis (Kays and Nottingham, 2008; Baldini et al, 2004, 2011).…”
mentioning
confidence: 99%
“…It is a good source of inulin, a sugar which is a linear mixture of oligosaccharides and polysaccharides [2]. The tuber can be used as a raw material for health food products-particularly for diabetics because inulin is not readily absorbed by humans-as well as in animal feed and bioethanol [3,4]. JA is currently classified as a functional food crop in tropical regions [5].…”
Section: Introductionmentioning
confidence: 99%